DIPG-74. RE-IRRADIATION OF DIPG: DATA FROM THE INTERNATIONAL DIPG REGISTRY. (4th December 2020) - Lafay-Cousin, Lucie; Lane, Adam; Schafer, Austin; Saab, Raya; Cheng, Sylvia; Bandopadhayay, Pratiti; Zaghloul, Mohamed; El-Ayadi, Motasem; Dorris, Kathleen; Packer, Roger; Kilburn, Lindsey; Minturn, Jane; et al.
Abstract: PURPOSE: To review data from DIPG Registry patients recorded to have received a second course of radiation therapy (rRT). METHODS: The International DIPG Registry was searched for patients with DIPG who were treated with a known dose of rRT. Doses of rRT, timing from initial diagnosis and primary radiation therapy (pRT), radiographic response to rRT and survival from diagnosis (OS) were evaluated. RESULTS: Sixty (11.2%) of 535 Registry patients underwent rRT; dose was provided for 44 patients. Median (range) data from those 44 revealed that rRT was given at 12 (2–65) months from initial diagnosis of DIPG and at 9.6 (1–61) months from completion of pRT at a dose of 26.7 (1.8–74) Gy. After completion of rRT, MRI showed response, progression, stable disease or was not available in 19, 8, 3 and 14 patients, respectively. Median PFS and OS were 11 and 18.1 months, respectively. 475 Registry patients did not undergo rRT; their ages, duration of symptoms, and primary treatment with or without chemotherapy were not significantly different from the rRT cohort. Median PFS and OS for the non-rRT patients were 6.9 and 10 months, respectively. rRT patients were more likely to have had radiographic evidence of tumor necrosis at diagnosis than non-rRT patients. CONCLUSIONS: Administration of rRT to patients with DIPG has been inconsistent with respect to timing and dose. Toxicity, response and quality of life data are incomplete, but survival appears to be lengthened with rRT. Prospective clinical trials will elucidate benefits and risks of rRT.